2012
DOI: 10.1080/10439463.2012.703198
|View full text |Cite
|
Sign up to set email alerts
|

Institutional racism and police reform: an empirical critique

Abstract: Institutional racism became a potent mobilising concept in police reform in the UK following the publication of the Stephen Lawrence Inquiry in 1999. Yet while it continues to be used to highlight problematic police/community relationships, little attention has been paid to whether it actually works as a conceptual instrument for change. The explanatory value of the concept has long been contested due to its inherent ambiguities: how, then, is it interpreted and applied by those charged with responding? Drawin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
0
31
0
1
Order By: Relevance
“…Gendered police roles and attitudes are bound up with embodied power, patriarchy, and machismo (Westmarland, 2017). In her police ethnographic work, Souhami (2014) found that women staff were subject to overtly exclusionary language that was not censured by their managers. Research also shows that a masculine ethos dominates police identity (Heidensohn, 1992).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Gendered police roles and attitudes are bound up with embodied power, patriarchy, and machismo (Westmarland, 2017). In her police ethnographic work, Souhami (2014) found that women staff were subject to overtly exclusionary language that was not censured by their managers. Research also shows that a masculine ethos dominates police identity (Heidensohn, 1992).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, police officers might experience bias and prejudice within the police because of core aspects of their identity such as religion, gender, age, disability and sexual orientation, and the intersectionality amongst these aspects of identity. Yet in the aftermath of the Macpherson Inquiry and the urgency of police responses, these experiences have not been a focus of attention; instead, there has been an intense focus on race thereby ignoringand thus sustainingother forms of exclusion within the police (Souhami, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In one instance, executives focused on emotions and personal feelings; in another instance, they focused on “external social structures related to personal attitudes and behavior, amplified by organizational cultures” (Holdaway and O'Neill :354). In most cases, it seems that the understanding of institutional racism became associated with the concept of sexist and racist “canteen culture,” the informal conversation away from public view (Souhami ). Institutional racism became misunderstood as a “quasi‐psychological” problem (Singh ; Souhami ; Wight ).…”
Section: Institutional Racism and Cognitive Biasmentioning
confidence: 99%
“…In most cases, it seems that the understanding of institutional racism became associated with the concept of sexist and racist “canteen culture,” the informal conversation away from public view (Souhami ). Institutional racism became misunderstood as a “quasi‐psychological” problem (Singh ; Souhami ; Wight ). “As a result it masks rather than illuminates the interplay between social structures, state power and individual action in creating and sustaining disadvantage, even though these are the very dynamics which the concept was originally formulated to describe” (Souhami :5).…”
Section: Institutional Racism and Cognitive Biasmentioning
confidence: 99%
“…The qualitative analysis presented below does not purport to say anything about the operation of police practices, since the data only concern perceptions of targeting, although perceptions are important in themselves (see, for example, Souhami, 2014). For the parents' survey, almost 40 per cent of respondents (17/44) said that their child had been stopped and searched (3/44 did not know), and 17/44 had themselves been stopped and searched.…”
Section: Age and Vulnerabilitymentioning
confidence: 99%